Upgrading existing databases: recommendations for irrigation districts - Flahive, David, author; Fipps, Guy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
All of the district in the Lower Rio Grande Valley currently store all of their accounting and water delivery records in computer databases. It has been known for several years that these database systems in the Lower Rio Grande Valley are in need of replacement. The current database systems are not compatible with modern software, including GIS and management software. Due to this lack of software compatibility the districts are unable to directly access the historic watering records in their databases. Without access to these records the districts are losing out on a valuable management and decision making tool. To determine the best upgrade option available, we considered the current database requirements of the district, as well as any foreseeable future requirements. We compared the costs and benefits of several free and commercially available database systems, taking into consideration software compatibility, ease of management, operating system requirements, and future software support. Based on our findings we are recommending upgrading to a Windows server running a SQL Server database. This configuration will give the districts the ability to fully utilize there existing datasets, while giving them the ability to be compatible with GIS and other management software.
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."